Nuclear Weapon Discussion on G20 Forum: A Media Framing Analysis From Kompas.com, BBC.co.uk, and Assyarqu Al-Awsathu Online Media - Maulana Ashari; Rohmah Akhirul Mukharom; Aditya Fahmi Nurwahid (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M) Institut Bisnis dan Komunikasi LSPR, 2023)
Indonesia holds a key role as host of the G20 Presidency in 2022. Many international media highlighted this summit and the issues that has been discussed inside.As a world economic forum, G20 Presidency in Indonesia also reviewed about the international security issue, one of it is nuclear weapon threat. This study identifies, analyze, and compares the content produced by Indonesia (Kompas.com), United Kingdom (BBC.co.uk), and Saudi Arabia’s online news media (aawsat.com), surrounding the frame of nuclear weapons issue on G20 Forum. The study utilizes the framing analysis model of Zhondang Pan and Gerald M. Kosicki, to explain the message that communicated by the three countries related on nuclear weapon issue on G20 summit. The major findings clearly captured that every media adopted different rhetorical frames through the media coverage of the G20 Presidency in Indonesia. Related on nuclear weapon issue, Indonesian media imply a neutral approach, different with UK’s media that used straightforward approach or Saudi’s media with interior approach.